ANALYSIS OF URBAN FORM AND INFRASTRUCTURE IN PALEMBANG - Johannes Adiyanto; Setyo Nugroho; Adhika Atyanta (Lembaga Penelitian dan Pengabdian pada Masyarakat (LPPM) Universitas Kristen Duta Wacana Yogyakarta, 2018)
Title: Analysis of Urban Form and Infrastructure in Palembang Analysis of physical characteristics of urban, which called urban form, can identify the shape, size, density, and configuration of settlements, which considered at the different scale: from regional to urban. In the different perspective, transportation shapes the cities. Based on these two concepts, this paper analyzing the growth of Palembang based on their infrastructure, especially transportation. This paper using the chronicles and narratives method with strategic overlay maps. The maps were arranged based on the years chronically and then analyzed the transportation infrastructure in that years. The results of this analysis, Palembang already growth based on the land transportation. The natural potential, the Musi River, was ignored. The main street, Jendral Sudirman street, become the ‘backbone’ of Palembang.